2016
DOI: 10.1073/pnas.1600968113
|View full text |Cite
|
Sign up to set email alerts
|

A RhoA and Rnd3 cycle regulates actin reassembly during membrane blebbing

Abstract: The actin cytoskeleton usually lies beneath the plasma membrane. When the membrane-associated actin cytoskeleton is transiently disrupted or the intracellular pressure is increased, the plasma membrane detaches from the cortex and protrudes. Such protruded membrane regions are called blebs. However, the molecular mechanisms underlying membrane blebbing are poorly understood. This study revealed that epidermal growth factor receptor kinase substrate 8 (Eps8) and ezrin are important regulators of rapid actin rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 39 publications
(39 reference statements)
7
62
1
Order By: Relevance
“…This is in line with our finding that RhoA and RhoB controlled different aspects of 3D amoeboid leukaemia cell migration, with RhoA being important for cell rear retraction, while RhoB controlled membrane blebbing. This contrasts with previous studies that have suggested a role for RhoA in cell membrane blebbing (Gadea et al , ; Godin & Ferguson, ; Cartier‐Michaud et al , ; Tozluoglu et al , ; Takahara et al , ; Bang et al , ; Aoki et al , ). However, in most of these studies, experimental methods (e.g.…”
Section: Discussioncontrasting
confidence: 82%
“…This is in line with our finding that RhoA and RhoB controlled different aspects of 3D amoeboid leukaemia cell migration, with RhoA being important for cell rear retraction, while RhoB controlled membrane blebbing. This contrasts with previous studies that have suggested a role for RhoA in cell membrane blebbing (Gadea et al , ; Godin & Ferguson, ; Cartier‐Michaud et al , ; Tozluoglu et al , ; Takahara et al , ; Bang et al , ; Aoki et al , ). However, in most of these studies, experimental methods (e.g.…”
Section: Discussioncontrasting
confidence: 82%
“…21 Taken together, we propose that the interlocked feedback system between Rnd3 and RhoA rapidly switches during membrane expansion to retraction in blebbing membrane. At the expanding plasma membrane, Rnd3 and RhoGAP are present at the plasma membrane and inhibit RhoA-ROCK activity.…”
Section: Rhoa-rock-rnd3 Feedback Loop Regulates the Expansion And Retmentioning
confidence: 59%
“…21 In the retracting phase of membrane blebs, we found that RhoA is activated at the plasma membrane. RhoA GTP-form and ROCK are recruited to the plasma membrane at the onset of bleb retraction.…”
Section: Rhoa-rock-rnd3 Feedback Loop Regulates the Expansion And Retmentioning
confidence: 81%
See 1 more Smart Citation
“…The knockout of ORP2 disrupted the F-actin organization of HuH7 cell and hampered cell adhesion, migration, and spreading of polarized lamellipodia. Instead of lamellipodia, the KO cells formed cell surface blebs, which may arise as a result of defective F-actin-plasma membrane interactions (41,42). The lamellipodia and migration defects in the ORP2-KO cells provide a plausible explanation for the growth mode of the KO cells, as the defects may result in an inability of the dividing cells to detach from one another and migrate, thus forming islet-like cell patches upon culture.…”
Section: Discussionmentioning
confidence: 99%